Privatization and Public Enterprises - Hemming, Richard (Occasional Papers; Occasional Paper ;, 1998)
This paper examines the role that privatization can play within a wider strategy designed to overcome the problems associated with public enterprises. For this purpose, privatization is defined as a transfer of ownership and control from the public to the private sector, with particular reference to asset sales. It is therefore equated with total or partial denationalization. Economic efficiency is not only the key to improving the performance of the public enterprise sector, but is also the source of other gains often attributed to privatization, in particular, its favorable budgetary impact. To public enterprises that are subject to national or international competition, privatization offers the possibility of increased productive efficiency as government financial backing is withdrawn and bankruptcy and takeover become possibilities. The admissibility and desirability of privatization, as well as what types of enterprise should be privatized, ought to be determined by similar considerations in both industrial and developing countries.